2006
DOI: 10.1590/s1806-83242006000100010
|View full text |Cite
|
Sign up to set email alerts
|

Effect of dentinal surface preparation on bond strength of self-etching adhesive systems

Abstract: ABSTRACT:The aim of this study was to evaluate the effects of dentin surface treatments on the tensile bond strength (TBS) of the self-etching primer Clearfil SE Bond (CSE) and the one-step self-etching One-Up Bond F (OUB). The exposed flat dentin surfaces of twenty-four sound third molars were prepared with diamond bur at high-speed, carbide bur at low-speed or wet ground with #600 grit SiC paper. The adhesive systems were applied to the dentin surfaces and light-cured according to the manufacturers' instruct… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
0
3

Year Published

2010
2010
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(13 citation statements)
references
References 13 publications
1
9
0
3
Order By: Relevance
“…4 Numerous studies have compared the surface morphology in cavities prepared using diamond and tungsten carbide burs and concluded that more surface roughness was evident in diamond bur preparation in comparison to tungsten carbide preparation. 2,5,25 The present study, confirming the above literatures also exhibited more surface roughness in diamond groups (1A and 1B) than in tungsten carbide groups (2A and 2B). However, although diamond produced greater surface roughness than tungsten carbide bur, it had a demerit of producing thick smear layer which might hinder bonding of restoration to enamel surface.…”
Section: Discussionsupporting
confidence: 91%
“…4 Numerous studies have compared the surface morphology in cavities prepared using diamond and tungsten carbide burs and concluded that more surface roughness was evident in diamond bur preparation in comparison to tungsten carbide preparation. 2,5,25 The present study, confirming the above literatures also exhibited more surface roughness in diamond groups (1A and 1B) than in tungsten carbide groups (2A and 2B). However, although diamond produced greater surface roughness than tungsten carbide bur, it had a demerit of producing thick smear layer which might hinder bonding of restoration to enamel surface.…”
Section: Discussionsupporting
confidence: 91%
“…Sondalama derinliği 4 mm den fazla olan dişlerde de etkin olmasına rağmen cep derinliği arttıkça başarı şansı düşer 6,39 . Ultrasonik aygıtlar ve el aletleriyle karşılaştırıl-dığında madde kaybı riskinin daha düşük olduğu bitirilmişse de 38 42 . Air polishing aygıtında sodyum bikarbonatın aşırı pürüz-lenmeye neden olmasından yola çıkılarak bu tür uygulamanın dentin bonding sistemlerine etkisi araştırılmış.…”
Section: Ultrasonik Ve Sonik Aletlerle Yapılan Diş Taşı Temizliği Ve unclassified
“…Carious dentin must be removed until a leathery consistency layer of dentin is reached promoting a successful and long-term survival of the restoration [1]. Whenever there is an abrasion or cut in the dental structure, a surface called smear-layer is formed, comprised of organic and inorganic materials, blood, saliva, oils from rotatory instruments, microorganisms and their products [2].…”
Section: Introductionmentioning
confidence: 99%